Distraction by emotion in early adolescence: affective facilitation and interference during the attentional blink - Heim, Sabine; Benasich, April A.; Keil, Andreas (Frontiers in Psychology, 2013)
This study examined the extent to which early adolescents (aged 10 to 13 years) differ from adults in their sensitivity to attention capture by affective stimuli during rapid processing. A rapid serial visual presentation paradigm (RSVP) was implemented as a dual task, requiring the report of two green target stimuli embedded in a stream of distractors. Known as the “attentional blink” (AB), task performance is typically impaired when the first and second targets (T1 and T2, respectively) are separated by at least one distractor and about 200 ms of time. Here we used written verbs of pleasant, neutral, and unpleasant content as T1 items, while affectively neutral exemplars served as T2 and distractor events. The temporal distance between T1 and T2 was manipulated to contain either one distractor (intertarget interval 232 ms) or five distractors (intertarget interval 696 ms). Students reported pleasant T1 words more accurately, compared to neutral and unpleasant words, indicating facilitation of appetitive content on performance during RSVP. Emotional relevance of T1 was at the expense of T2 accuracy: At an intertarget interval of 232 ms (i.e., during the AB period), identification of (neutral) T2 words was impaired when preceded by pleasant and unpleasant T1s. No interference across targets was observed, however, beyond the blink period, in which T1 and T2 were separated by 696 ms. Thus, emotionally relevant events capture and hold attentional resources, at the cost of attentive processing in subsequent episodes. Contrary to our findings in adults, these capture effects were most obvious when the available capacity was limited, i.e., during the critical interval of the AB. The findings are discussed in light of the use of alternative cognitive strategies as development proceeds beyond early adolescence into adulthood.